Performance optimization of ice thermal storage device based on micro heat pipe arrays. (May 2022) - Liu, Zichu; Quan, Zhenhua; Zhao, Yaohua; Jing, Heran; Yang, Mingguang
Abstract: Ice thermal storage device using micro heat pipe arrays and closed rectangular fins has been proven to exhibit excellent thermal performance. However, neither the details of ice formation inside the device nor the dominant factors affecting the performance of the device and the optimal fin geometric parameters, have been reported. In this study, numerical simulations were performed to investigate the ice packing factor, dynamic ice front evolution, and effects of fin geometric parameters including fin height, thickness, and spacing on the thermal performance of the proposed device. Results demonstrated that the fins effectively improved ice formation homogeneity and accelerated ice formation. The decreased fin height and spacing, increased fin thickness were positive to enhance thermal characteristics. Taguchi method was used to obtain the contribution ratio of independent fin parameter and optimal geometric fin configuration to the thermal performance. Fin thickness played a dominant role with a contribution rate of up to 44.52%, followed by 28.65% for fin height and 26.83% for fin spacing. From the perspective of trade-off between ice formation rate and manufacturing cost, the optimal height, spacing, and thickness of the fin structure for practical engineering application were determined to be 15, 10.1, and 0.25 mm, respectively. Highlights: The heat transfer characteristics of MHPA-ITSD during ice formation process was analyzed. Effect of height, spacing and thickness of closed rectangular fins are numerical investigated. Fin thickness plays a leading role in the ice thermal storage efficiency. The optimal parametric combination of closed rectangular fins is given using Taguchi method.